Effects of postharvest dipping of sodium hypochlorite and hydro-cooling on the quality of ‘Petomech’ tomato fruits - Mani, V P; Rahaman, A Abdul; Nimbare, A C; Y. I. Buonamwen, Y I; Musah, K; Wahab, S Abdul; Ghulam, K (Journal of Postharvest Technology, 2023)
A continuing increase in the demand for fresh and processed tomatoes in Ghana from national and international supply points is an indication of the importance of the crop in the fresh produce and retail sectors. The handling of tomato fruits comes with ripening variability which contributes to the faster deterioration during storage. The physiochemical quality of ‘Petomech’ tomato variety in response to different concentrations of sodium hypochlorite (NaOCl) and hydro-cooling treatments were studied during short term storage at ambient temperature of 25.9°C and relative humidity of 80-85%. The NaOCl at 0, 5% and 10% were applied. Fruits were hydro-cooled by immersion for 15 minutes in water at 23.7°C, agitated water at 20.5°C and non-cooled. The results demonstrated that tomato fruits treated with the combined NaOCl at 5% and hydro-cooling with agitated water significantly delayed weight changes, maintained firmness and gave better soluble solids, titratable acidity and pH compared to uncoated fruits (P ≤ 0.05). For disease incidence higher beneficial effects were found due to interaction of NaOCl at 5% and hydro-cooling with agitated water (4.47%). Fruits not treated with NaOCl and hydro-cooling gave a significant higher incidence of 33.35%. Based on the results of this study, it was concluded that the combination of NaOCl at 5% as disinfectant and hydro-cooling with agitated water can be applied for short term storage of ‘Petomech’ tomato fruits. It was also established that treatments can be used as an effective technology to reduce the activity of opportunistic organisms that cause disease incidence at storage.